The Effects of a Systematically Designed Online Learning Environment on Preservice Teachers' Professional Knowledge. Issue 3 (3rd July 2017) - Evens, Marie; Larmuseau, Charlotte; Dewaele, Katrien; Van Craesbeek, Leen; Elen, Jan; Depaepe, Fien
Abstract: This study examines the effects of an online learning environment on preservice teachers' pedagogical content knowledge (PCK), content knowledge (CK) (related to French in primary teacher education), and pedagogical knowledge (PK) in a quasi-experimental design. More specifically, the following research question is addressed: Is a systematically developed online learning environment more effective in promoting PCK, CK, and PK than an alternative face-to-face and self-study program? The results show that after controlling for prior knowledge, the online learning environment had a more positive impact on preservice teachers' PCK and PK than the alternative program. However, for CK no significant differences between the two learning environments were found.